2010
DOI: 10.1002/cbdv.200900343
|View full text |Cite
|
Sign up to set email alerts
|

Locked Nucleic Acids: Promising Nucleic Acid Analogs for Therapeutic Applications

Abstract: Locked Nucleic Acid (LNA) is a unique nucleic-acid modification possessing very high binding affinity and excellent specificity toward complementary RNA or DNA oligonucleotides. The remarkable properties exhibited by LNA oligonucleotides have been employed in different nucleic acid-based therapeutic strategies both in vitro and in vivo. Herein, we highlight the applications of LNA nucleotides for controlling gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
138
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(139 citation statements)
references
References 52 publications
0
138
0
1
Order By: Relevance
“…anti-microRNAs (antagomirs), and anti-gene approaches (34,35). An LNA-containing ON with its 3′-endo conformation is considered to be an RNA mimic, making it effective toward structured RNA regions, which can be beneficial when targeting pre-mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…anti-microRNAs (antagomirs), and anti-gene approaches (34,35). An LNA-containing ON with its 3′-endo conformation is considered to be an RNA mimic, making it effective toward structured RNA regions, which can be beneficial when targeting pre-mRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Another way to address this problem is to assemble carbohydrate-modified ONs, exemplified by hexitol nucleic acids [10][11][12][13][14], 2'-O-(2-methoxy)ethyl ONs [15,16] and bicyclic ONs [17], with the LNA monomers of the Wengel group [18] showing the strongest affinity for RNA, and having many alternative structures [19]. The strong hybridization characteristics between these structures and complementary RNA are generally attributed to the formation of a preorganized conformation, fitting the A-form of dsRNA, with strong stacking interactions between the bases, adequate interaction of the latter in a Watson-Crick type geometry with their complement, and efficient hydration of the double-stranded helix [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most prominent examples are 2 0 -fluoro (2 0 -F), 107,108 2 0 -O-methyl (2 0 -OMe), 109 2 0 -methoxyethyl (2 0 -MOE), 110,111 2 0 -fluoroarabino (2 0 -FANA), 112 locked nucleic acid (LNA), 113,114 unlocked nucleic acid (UNA), 115,116 cyclohexenyl (CeNA) nucleic acid, 117,118 peptide nucleic acid (PNA), 119 phosphoramidate morpholino (PMO) 120 etc. Although many of the modified nucleotides have been successfully utilized in various nucleic acid-based therapeutic technologies, their relatively poor or no enzymatic recognition properties often pose a major challenge toward the development of biostable aptamers.…”
Section: Chemically Modified Aptamer-oligonucleotide Chimeramentioning
confidence: 99%
“…[127][128][129][130][131][132][133][134] LNA is one of the successful nucleotide analogs extensively utilized in various fields because of their remarkable properties. 113,114 In LNA the sugar ring is conformationally locked by a O2 0 -C4 0 methylene linkage to adopt N-type sugar puckering. [135][136][137] Toward developing LNA-modified aptamers, Veedu et al reported the enzymatic recognition capabilities of LNA nucleotides using DNA and RNA polymerases.…”
Section: Chemically Modified Aptamer-oligonucleotide Chimeramentioning
confidence: 99%